1989
DOI: 10.1152/ajpgi.1989.257.2.g221
|View full text |Cite
|
Sign up to set email alerts
|

Differential action of somatostatin on peptide-induced release of acetylcholine

Abstract: In this study we examine the mechanism by which somatostatin (SRIF-14) inhibits cholecystokinin octapeptide- (CCK-8) but not substance P-mediated release of [3H]acetylcholine (ACh) from the guinea pig ileum. 2',5'-Dideoxyadenosine, an inhibitor of adenylate cyclase, antagonized the action of CCK-8 and forskolin but had no effect on substance-P-evoked release of [3H]ACh. Addition of theophylline enhanced the release of [3H]ACh stimulated by CCK-8 but not by substance P. These observations suggest that CCK-8, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although it is not well known, one of the suggested mechanisms for the octreotide-induced long QT interval is slowdown of the conducting system due to its inhibitory effects on sinoatrial and atrioventricular nodes via somatostatin receptors [16,17,18,19,20]. The recognition of a long QT interval during octreotide treatment and recovery of the interval after discontinuation led us to suggest that in our case long QT development was secondary to octreotide treatment.…”
Section: Discussionmentioning
confidence: 75%
“…Although it is not well known, one of the suggested mechanisms for the octreotide-induced long QT interval is slowdown of the conducting system due to its inhibitory effects on sinoatrial and atrioventricular nodes via somatostatin receptors [16,17,18,19,20]. The recognition of a long QT interval during octreotide treatment and recovery of the interval after discontinuation led us to suggest that in our case long QT development was secondary to octreotide treatment.…”
Section: Discussionmentioning
confidence: 75%
“…So, these investigations describe the two main kinds (SOM-positive and Met-enkephalin-positive) of inhibitory neurons, which have distinct neuromodulatory functions in the cholinergic pathways within the ENS. It has also been shown that SOM-induced relaxation of the intestinal muscles is connected with the pre-synaptic inhibition of acetylcholine release by different mechanisms [125,126]. The main mechanism of this SOM activity results from the inhibitory effects on 3’,5’-cyclic adenosine monophosphate [125,126].…”
Section: Functions Of Somatostatin In the Enteric Nervous Systemmentioning
confidence: 99%
“…It has also been shown that SOM-induced relaxation of the intestinal muscles is connected with the pre-synaptic inhibition of acetylcholine release by different mechanisms [125,126]. The main mechanism of this SOM activity results from the inhibitory effects on 3’,5’-cyclic adenosine monophosphate [125,126]. A similar activity of SOM was observed in the submucous plexuses, where in the guinea pig intestine SOM caused the hyperpolarization of about 90% of the total neuronal population [127].…”
Section: Functions Of Somatostatin In the Enteric Nervous Systemmentioning
confidence: 99%
“…For receptor antagonism experiments, the antagonist was administered followed in 7 min by application of the control dose of agonist in the continued presence of the antagonist. For the experiments with pertussis toxin, the procedure of Kowal et al (14) was used, with incubation of the tissue with pertussis toxin at 200 ng/ml for 3 h. A higher dose of pertussis toxin (1 g/ml) for 3 h was also used. For the experiments with zero calcium, a procedure we have previously used was employed (19), with switching the Krebs solution surrounding the muscle strip to zero calcium with 0.1 mM EGTA for 4 min before the addition of PAF.…”
Section: Methodsmentioning
confidence: 99%